ROMATOİD ARTRİTLİ HASTALARDA STEROİD İYONTOFOREZİNİN ETKİNLİĞİNİN DEĞERLENDİRİLMESİ - GÜLKESEN, ARİF (Fırat Üniveristesi, 2005)
current treatment and flow characteristics assessed using PDUS did not significantly change with these treatments. Key words: Rheumatoid arthritis, steroid iontophoresis, direct currect, power Doppler ultrasound.

ASSESSMENT OF THE EFFICACY OF STEROID IONTOPHORESIS IN PATIENTS WITH RHEUMATOID ARTHRITIS Aims: This study is a comparative assessment of direct galvanic current and steroid iontophoresis to the wrist joints in patients with rheumatoid arthritis (RA). Background: Rheumatoid arthritis is a chronic inflammatory disease involving hand and wrist joints symmetrically, and causes pain, swelling, restriction in joint motions resulting limitations in daily living activities. Methods: Twenty patients with active synovitis in wrist joints have been included into the study. One wrist of a patient was treated with steroid iontophoresis and the opposite side was treated with galvanic current as the control side. Patients' pre- and post-treatment measurements of pain- V AS, patient's and physician's global assessment of disease severity (Visual analog scale- V AS), tender joint counts, swollen joint counts, hand grip strength (GS), lateral pinch strength (LGS), joint circumference of the wrist and interphalangeal joints (2-5), range of motion (ROM) of wrist, metacarpophalangeal (2-5) and interphalangeal joints (2-5), hand functional score (HFS), Health Assessment Questionnaire (HAQ), Nottingham Health Profile (NHP), Ritchie Articular Index (RAI), Disease Activity Score-28 (DAS-28), Duruöz Hand Index (DHI) and power Doppler ultrasonography (PDUS) of targeted joints were assessed. Results: There was significant improvement with the treatment in clinical and laboratory measurements which allowed global assessment of the patients as ESR, CRP, VAS, HAQ, DAS-28, NHP, and DHI. Significant improvements were achieved in steroid treated and control wrists in HG, LHG, HFS, circumference and ROM of hand and wrist joints, swollen and tender joint counts. But the improvement estimated as the differences between post and pre-treatment measurements in steroid treated and control wrists were not significant compared to each other. Additionally, PDUS measurements assessed in joints that had pannus and quantifiable flow did not have significant changes with either stertoid iontophoresis or direct galvanic current. Conclusion: Our results indicate that steroid iontophoresis given to the rheumatoid arthritis patients' wrists with active synovitis is not superior to galvaniccurrent treatment and flow characteristics assessed using PDUS did not significantly change with these treatments. Key words: Rheumatoid arthritis, steroid iontophoresis, direct currect, power Doppler ultrasound.
Assessment of the efficacy of steroid iontophoresis in patients with rheumatoid arthritis
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Fiziksel Tıp ve Rehabilitasyon